The Formation Of Student's Character In The Perspective Of The Al-Qur'an - Mardia Ulfa Hasibuan; Ela Syahfriani (Proceeding International Seminar of Islamic Studies, 2019)
This research entitled the formation of students' character in the perspective of the Alquran. The problem that arises is that there are many students who have committed acts that are not commendable to the teachers in the school or even friends who are in the school environment. many of us encounter in the present time like a student who is against his teacher. This is different from the past. At the present time a teacher cannot do more in terms of handling students in school. Because parents today feel more powerful and have more rights towards their children. Besides that at the present time many of us encounter a student who is bullying his classmates. Whether students have problems with the teacher or friends so that there is no good relationship with them. As for the purpose of this study is to find out how to shape the character of good students based on the Alquran and also reduce the problems that arise at this time. The method used is Library Research, qualitative. It was found that the way to shape the character of good students varied according to the Alquran.